Adherence to human epidermal growth factor receptor-2 testing and adjuvant trastuzumab treatment guidelines in Ontario. (March 2020) - Marshall, Deborah A; Ferrusi, Ilia L; Trudeau, Maureen; Leighl, Natasha B; Hoch, Jeffrey S; Grazziotin, Luiza R; Khong, Hoa; Pullenayegum, Eleanor; Earle, Craig C
Objectives: We evaluated adherence of human epidermal growth factor receptor-2 testing using immunohistochemistry and fluorescence in situ hybridization, as well as adjuvant trastuzumab treatment according to Canadian guidelines, and predictors of trastuzumab use in early-stage breast cancer in Ontario. Methods: Retrospective cohort of early-stage breast cancer patients identified in the Ontario Cancer Registry. Human epidermal growth factor receptor-2 test type, sequence, result(s), tumor grade, and hormone receptor status were abstracted from Ontario Cancer Registry pathology reports. Trastuzumab treatment was determined from provincial cancer agency records. Other variables were determined from administrative data sources. Logistic regression models were used to estimate adjusted odds ratios for factors associated with guideline adherence. Results: The first human epidermal growth factor receptor-2 test result was the strongest predictor of confirmatory testing ( p  < 0.05). Human epidermal growth factor receptor-2 testing by immunohistochemistry accounted for the majority of documented first tests (94%; n  = 8249). Overall, 27% ( n  = 2360) of tested patients received a second test by fluorescence in situ hybridization (46%) or immunohistochemistry (49%) assay. Most human epidermal growth factor receptor-2 equivocal patients (89%; n  = 784) received a confirmatory test. Among human epidermal growth factor receptor-2-positive patients, only 57% ( n  = 385) received trastuzumab treatment within the study period. Human epidermal growth factor receptor-2 status was the strongest predictor of trastuzumab use. Younger patients (<70 years at diagnosis) and negative hormone receptor status had higher odds of trastuzumab treatment ( p  < 0.05) compared to older and positive hormone receptor status patients. Conclusions: Immunohistochemistry use as a first test was largely consistent with Canadian guidelines; however, immunohistochemistry was frequently used as a confirmatory test, which is not guideline-concordant. Monitoring these testing and treating patterns is necessary to optimize health outcomes associated with trastuzumab.